2018
DOI: 10.1080/15592324.2018.1441657
|View full text |Cite
|
Sign up to set email alerts
|

Particle bombardment – mediated gene transfer and GFP transient expression in Setaria viridis

Abstract: Setaria viridis is one of the most important model grasses in studying monocot plant biology. Transient gene expression study is a very important tool in plant biotechnology, functional genomics, and CRISPR-Cas9 genome editing technology via particle bombardment. In this study, a particle bombardment-mediated protocol was developed to introduce DNA into Setaria viridis in vitro leaf explants. In addition, physical and biological parameters, such as helium pressure, distance from stopping screen to the target t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Agrobacterium tumefaciens infection have been demonstrated (Brutnell et al 2010;Van Eck et al 2017;Mookkan 2018;Van Eck 2018). Historically, much of the Setaria literature referred to A10 for phenotypic evaluation, which made selecting it for whole genome sequencing a logical choice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agrobacterium tumefaciens infection have been demonstrated (Brutnell et al 2010;Van Eck et al 2017;Mookkan 2018;Van Eck 2018). Historically, much of the Setaria literature referred to A10 for phenotypic evaluation, which made selecting it for whole genome sequencing a logical choice.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient genetic modification is a primary requirement for development of any model organism. Approaches for Setaria protoplasting, particle bombardment, and Agrobacterium tumefaciens infection have been demonstrated ( Brutnell et al 2010 ; Van Eck et al 2017 ; Mookkan 2018 ; Van Eck 2018 ). Historically, much of the Setaria literature referred to A10 for phenotypic evaluation, which made selecting it for whole genome sequencing a logical choice.…”
mentioning
confidence: 99%
“…S3). In previous studies, particles coated with large amounts of DNA had low membrane permeability due to particle aggregation [21], and a high concentration of cationic peptide induced cytotoxicity in plant cells [14]. These results suggested that the expression levels induced by 16 and 24 µg of DNA-peptide complex per bombardment were remarkably decreased.…”
Section: Effect Of Dna-peptide Complex Load Per Bombardment In B Camp...mentioning
confidence: 82%
“…The cotyledons of B. campestris were bombarded once or twice to analyze the efficiency of Nluc expression. Several reports indicated that multiple bombardments affected gene transfer efficiency in various plant species [21][22][23]. Nluc expression induced by two bombardments was significantly lower than that induced by one bombardment (P = 0.0100, Fig.…”
Section: Effect Of the Number Of Bombardments In B Campestrismentioning
confidence: 95%
“…Then, the particles are accelerated to very high velocity for bombardment. Such a high momentum of metal particles causes substantial damage to the chloroplasts after particle bombardment on explants (Russel et al, 1992;Mookkan, 2018). In this study, we contemplated establishing reliable and effective potato plastome engineering protocol through the incorporation of the marker gene into the potato plastome.…”
Section: Discussionmentioning
confidence: 99%